2012
DOI: 10.1002/hbm.22199
|View full text |Cite
|
Sign up to set email alerts
|

The human amygdala and pain: Evidence from neuroimaging

Abstract: The amygdala, a small deep brain structure involved in behavioral processing through interactions with other brain regions, has garnered increased attention in recent years in relation to pain processing. As pain is a multidimensional experience that encompasses physical sensation, affect, and cognition, the amygdala is well suited to play a part in this process. Multiple neuroimaging studies of pain in humans have reported activation in the amygdala. Here we summarize these studies by performing a coordinate-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
201
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(206 citation statements)
references
References 63 publications
4
201
0
1
Order By: Relevance
“…Chronic pain is an ideal model used to understand these types of conditions in the context of localized and integrated neural networks. The brain regions implicated in chronic pain and anxiety include somatosensory cortex, anterior cingulate cortex, prefrontal cortex, and amygdala (Apkarian et al, 2004;Lee and Tracey, 2013;Simons et al, 2014aSimons et al, , 2014b. Emotional disorder and pain possibly share the same biological pathways and neurotransmitters, which influence concurrent treatments (Blier and Abbott, 2001).…”
Section: Chronic Pain and Anxietymentioning
confidence: 98%
“…Chronic pain is an ideal model used to understand these types of conditions in the context of localized and integrated neural networks. The brain regions implicated in chronic pain and anxiety include somatosensory cortex, anterior cingulate cortex, prefrontal cortex, and amygdala (Apkarian et al, 2004;Lee and Tracey, 2013;Simons et al, 2014aSimons et al, , 2014b. Emotional disorder and pain possibly share the same biological pathways and neurotransmitters, which influence concurrent treatments (Blier and Abbott, 2001).…”
Section: Chronic Pain and Anxietymentioning
confidence: 98%
“…The amygdala is indeed a relevant element in the processing of pain, but its activation is highly variable in pain experiments 36 . Only a small proportion of previous imaging studies have reported significant changes in the amygdala, which involved both signal increases and decreases according to a recent metaanalysis 36 . Thus, the finding of no net amygdala activation during pain provocation in our study is not an unexpected finding.…”
Section: Journal Of Rheumatologymentioning
confidence: 99%
“…Based on previous studies, nine brain areas (regions involved in pain processing and being part of the CAN) were initially considered as ROIs: left and right insula, left and right thalamus, left and right medial prefrontal cortex (MPFC), anterior division of cingulate gyrus, amygdala and hypothalamus [5,11,22,31,36,37,47]. However, our group-level analysis in the present study, showed no significant pain-related activity in the amygdala or hypothalamus (see the Results section).…”
Section: Fmri Data Processingmentioning
confidence: 99%